Complications and reoperations related to tension band wiring and plate osteosynthesis of olecranon fractures - Rantalaiho, Ida K.; Laaksonen, Inari E.; Ryösä, Anssi J.; Perkonoja, Katariina; Isotalo, Kari J.; Äärimaa, Ville O. (Journal of shoulder and elbow surgery, 2021)
Olecranon fractures are common and usually treated operatively either by tension band wiring (TBW) or plate fixation (PF). The aim of this study was to assess early complications and reoperations and their predictive factors related to those operative methods. A retrospective analysis of all patients with an operatively treated olecranon fracture between 2007 and 2017 at Turku University hospital was performed. Reoperations, postoperative complications, and potential risk factors for these were recorded. A total of 434 patients (387 TBW and 47 PF) were identified. There was no statistically significant difference in the rate of early complications (49% vs. 62%, P = .262) or reoperations (38% vs. 53%, P = .079) between patients treated with TBW and PF. In the TBW group, the intramedullary placement of Kirschner (K)-wires predisposed patients to complications compared to transcortical placement of the K-wires according to multivariate analysis (odds ratio [OR] 1.94, P = .026). Younger age was associated with the frequency of reoperations, the odds decreasing 24% for every 10 years of age (P < .001). Further, patients with high-energy trauma mechanisms were reoperated more often compared to patients with low-energy trauma (OR 2.99, P = .002). Also, excellent postoperative reduction was associated with higher reoperation rate than good or fair reduction (OR 0.48, P = .033). There is a high risk of early complications and reoperations associated to both TBW and PF. Transcortical positioning of K-wires may reduce the rate of complications in TBW.